2004
DOI: 10.1029/2004ja010397
|View full text |Cite
|
Sign up to set email alerts
|

A simple model of the flux content of the distant magnetotail

Abstract: A simple model is presented which allows the profile of open flux within the magnetotail lobes to be determined from a knowledge of the present size of the polar cap and the past history of low‐latitude and high‐latitude dayside reconnection. The model shows that the nominal length of the tail is dependent on the elapsed time since reconnection of the oldest open field lines and that a much longer disconnected tail and wake can exist beyond this. The model is applied to two 8‐hour intervals of observations, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 32 publications
4
46
1
Order By: Relevance
“…Recent studies have employed observations of the polar ionosphere to determine the quantity of open flux contained within the northern polar cap (Milan et al, 2003Milan, 2004). Taken from these studies, Figs As proposed by Levy et al (1964) and demonstrated by Holzer and Slavin (1979), Holzer et al (1986), Milan (2004 and Milan et al (2004), the dayside reconnection rate can be approximated by…”
Section: Methodology and Observationsmentioning
confidence: 91%
“…Recent studies have employed observations of the polar ionosphere to determine the quantity of open flux contained within the northern polar cap (Milan et al, 2003Milan, 2004). Taken from these studies, Figs As proposed by Levy et al (1964) and demonstrated by Holzer and Slavin (1979), Holzer et al (1986), Milan (2004 and Milan et al (2004), the dayside reconnection rate can be approximated by…”
Section: Methodology and Observationsmentioning
confidence: 91%
“…Milan et al (2004) showed that the tail inflates and deflates as the polar cap expands and contracts. In addition, knowing the size of the polar cap and the past rates of dayside and nightside reconnection, allow the length and flux content of the distant magnetotail to be deduced (Milan, 2004a). Such observations are a powerful tool for the diagnosis of the state of the terrestrial magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The time derivative of is an electric voltage in application of Faraday's law: it is the net reconnection voltage. This voltage relates to the electric field measured along the moving open/closed field line boundary taken at any altitude (Siscoe and Huang, 1985; see also Grocott et al, 2002;Milan et al, 2003Milan et al, , 2004Milan, 2004;Hubert et al, 2006a, and electric voltage that corresponds to the rate of change in the magnetic flux through any surface delineated by that closed curve and in particular in the open magnetic flux threading the polar cap delineated by the moving open/closed field line boundary detected at ionospheric altitude. This electric field has two contributions: the ionospheric field and the motional field that accounts for the motion of the boundary.…”
Section: Discussionmentioning
confidence: 99%